Judicial politics in new democracies : cases from Southern Africa - VonDoepp, Peter, 1967- (Boulder, Colo. : Lynne Rienner Publishers, 2009)
"That judicial institutions are important for emerging democracies leaves little (if any) room for debate. But to what extent do judiciaries in these new democracies maintain their autonomy? And what accounts for varying levels of autonomy across states? Drawing on the cases of Malawi, Zambia, and Namibia - and offering a novel analytical framework - Peter VonDoepp illuminates why power holders behave as they do toward the courts." "VonDoepp considers whether and why political leaders have respected or undermined judicial autonomy in each of the three cases. He also addresses how the courts themselves have shaped executive-judicial relations. His findings present unexpected challenges for existing frameworks, as well as important lessons about the factors and conditions affecting judicial development in transitional states."--BOOK JACKET.
Democracy and judicial autonomy : investigating the Southern African cases -- Understanding government choices : judicial politics in theoretical perspective -- Neopatrimonial politics and the intimidation of the courts in Zambia -- Informal ties, threats, and the problem of judicial control in Malawi -- Party dominance and judicial autonomy in Namibia -- Insights from the Southern African cases.
Includes bibliographical references (p. 169-178) and index.
Keywords: Justice, Administration of -- Africa, Southern